Effect of Annealing on Optical Properties of Zinc Oxide Thin Films Prepared by Homemade Spin Coater - Mulmi, Deependra Das; Dhakal, Agni; Shah, Buddha Ram (Nepal Journal of Science and Technology, 2015)
Zinc oxide (ZnO) thin films were deposited on the ordinary glass substrates by spin coating method. The precursor solution was prepared by mixing zinc acetate dehydrate in appropriate proportions with ethanol and diethanolamine (DEA). The obtained thin films were dried at 200°C for 15 minutes in hot air oven. Crystalline ZnO thin films were achieved following annealing process at temperatures 300°, 400° and 500°C for 2 hours. Thin films as- prepared were studied by X-ray diffraction and UV-visible spectroscopy. The films were transparent from near ultraviolet to infrared region. Optical band gap energy of ZnO was obtained 3.22 eV at 300°C. On annealing at 400° and 500°C, band gap energy was shifted at 3.14 eV and 3.05 eV respectively. DOI: http://dx.doi.org/njst.v15i2.12126 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 111-116